The Relationship Compliance with Iron Tablet Consumption with the incidence of anemia in Pregnant Women in the working area of the Tanjung Pati Health Center, Nagari Sarilamak in 2022 - Primadella Fegita; Muhammad Rizki Saputra; Lathifah Ainil Hakim (Andalas Obstetrics And Gynecology Journal, 2023)
Backgrounds: Anemia prevention program for pregnant women in Indonesia by giving 90iron tablets during pregnancy. However, pregnant women’s refuse or don’t comply with thisadvice for various reasons so that prevalence of anemia in pregnant women is still high.Purpose: To determine the relationship beetween adherence to consuming iron tablets andthe incidence of anemia in pregnant women in the Tanjung Pati Nagari Sarilamak HealthCenter in 2022.Methods : The scope of this research is Obstetrics and Gynecological science. The study wasconducted in June - July 2022. The type of research is cross sectional study. The affordablepopulation in the study was pregnant women in the Tanjung Pati Nagari Sarilamak HealthCenter working area as many as 74 samples with accidental sampling technique. Univariatedata analysis is presented in the form of frequency distribution and bivariate analysis usingthe Kolmogorov-Smirnov, data processing using the computerized SPSS version IBM 25.0.Results: the highest pregnant women age is 20-35 years, which is 58 people (78.4%), thehighest education is high school, which is 32 people (43.2%). The highest parity pregnantwomen is multipara, which is 30 people (40.5%), the highest gestational age in the 2ndtrimester, which is 35 people (47.3%), pregnant women who are not anemic, which is 60people (81.1%), pregnant women with compliance consuming iron tablets was good, which is58 people (78.4%), and the relationship between adherence to consuming iron tablets and theincidence of anemia in pregnant women in the Tanjung Pati Nagari Sarilamak Health CenterWork Area in 2022 (p = 0.000).Conclusion: There is a relationship between the compliance of pregnant women inconsuming iron tablets and the incidence of anemia in the Tanjung Pati Nagari SarilamakHealth Center Work Area in 2022